Wild Meat Is Still on the Menu: Progress in Wild Meat Research, Policy, and Practice from 2002 to 2020 - Ingram, D.J.; Coad, L.M.; Milner-Gulland, E.G.; Parry , L.; Wilkie, D.; Bakarr, M.I.; Benítez-López, A.; Bennett, E.L.; Bodmer, R.; Cowlishaw, G.; El Bizri, H.R.; Eves, H.E.; et al. (Annual Reviews, 2021)
Several hundred species are hunted for wild meat in the tropics, supporting the diets, customs, and livelihoods of millions of people. However, unsustainable hunting is one of the most urgent threats to wildlife and ecosystems worldwide and has serious ramifications for people whose subsistence and income are tied to wild meat. Over the past 18 years, although research efforts have increased, scientific knowledge has largely not translated into action. One major barrier to progress has been insufficient monitoring and evaluation, meaning that the effectiveness of interventions cannot be ascertained. Emerging issues include the difficulty of designing regulatory frameworks that disentangle the different purposes of hunting, the large scale of urban consumption, and the implications of wild meat consumption for human health. To address these intractable challenges, we propose eight new recommendations for research and action for sustainable wild meat use, which would support the achievement of the United Nations Sustainable Development Goals.